Failure tests on concrete bridges: Have we learnt the lessons?. Issue 3 (4th March 2018) - Bagge, Niklas; Popescu, Cosmin; Elfgren, Lennart
Abstract: Full-scale failure tests of bridges are important for improving understanding of bridges' behaviour and refining assessment methods. However, such experiments are challenging, often expensive, and thus rare. This paper provides a review of failure tests on concrete bridges, focusing on lessons from them. In total, 40 tests to failure of 30 bridges have been identified. These include various types of bridges, with reinforced concrete or prestressed concrete superstructures, composed of slabs, girders and combinations thereof. Generally, the tests indicated that theoretical calculations of the load-carrying capacity based on methods traditionally used for design and assessment provide conservative estimates. It can also be concluded that almost a third of the experiments resulted in unexpected types of failures, mainly shear instead of flexure. In addition, differences between theoretical and tested capacities are often apparently due to inaccurate representation of geometry, boundary conditions and materials.